Canvassing the aetiology, prognosis and molecular signatures of obstructive sleep apnoea. (2nd January 2019) - Khurana, Sartaj; Sharda, Shivani; Saha, Biswajit; Kumar, Sachin; Guleria, Randeep; Bose, Sudeep
Abstract: Context: Obstructive sleep apnoea (OSA) is a sleep respiration disorder with multiple pathophysiological risks. The study of OSA is important from a public health perspective due to increased risk of cardiovascular morbidity and metabolic disorders. Objective: The review content contributes to amalgamate the clinico-molecular analysis of microRNAs, single-nucleotide polymorphisms (SNPs), transcriptome profiles and epigenetics in the prognosis of OSA. The conceptual focus here is to demarcate the involvement of regulatory players like miRNAs that have most probable contributions towards other changes in patients leading to clinical outcomes. Methods: Literature survey was done by retrieving data from databases such as Google Scholar, PubMed and Science Direct. Results: Abundant reports have suggested the involvement and role of biomarkers such as CRP, TNF-α, IL-6, IL-8 and CAMs but there are interspersed speculations about the involvement of epigenetics in OSA. Conclusions: miRNA and transcriptome profiling, DNA methylation and SNPs are some of the less researched aspects that aim to bridge the gap in the molecular mechanisms underlying the pathophysiology of OSA. The quest for biomarkers in OSA is now distinctly achieving new heights. In the context of diagnosis, the above mentioned epigenetic regulators are likely to emerge as viable contenders.